Penentuan Penerima Bantuan Pangan Non Tunai (BPNT) Menerapkan Metode Multi Objective Optimization on the Basis of Ratio Analysis (MOORA) - Ahmad Yanda; Mesran Mesran (PDSI, 2022)
Non-Cash Food Assistance (BPNT) is something that is made as assistance in the form of food, to help the community, especially in social services that are given to the community in a non-cash way or called electronic money whose source is the government and is given to underprivileged families or beneficiary families. (KPM). This assistance is distributed every month using a card and exchanged at e-Warong. The result of the exchange is food or in the form of rice, milk, instant noodles etc. In the process of selecting candidates for BPNT assistance, it will be very difficult if it is decided manually. Therefore, a system called DSS is needed. Decision Support System (DSS) is a stage in finding a solution to a problem where the process is carried out using a solution according to how the computer works. DSS can work optimally if using the method. In this study, the authors chose the Multi-Objective Optimization Method on The Basic of Ratio Analysis (MOORA) which is a method that can be used in the completion and completion process of the DSS. This method has a working procedure that uses mathematical calculations. The results of this study were obtained as the best candidate for the recipient of BPNT funds, alternative A4 on behalf of Jefri with a value of 0.2362 as the first rank